Comparative Analysis of Accepted Criteria for Routine Test of Aluminothermic Welds for Electrified Double Track Project (EDTP) Gemas to Johor Bahru - Azamuddin, Azamuddin; Prasetijo, PROF. MADYA Ts Joewono; Mohamed Jizi, Siti Zarini (Progress in Engineering Application and Technology, 2024)
Thermite welding, commonly referred to as aluminothermic welding, is a method of joining metal pieces by creating molten metal through a chemical reaction between aluminium oxide and aluminium powder. The correct management of porosity to weld is a common problem in aluminothermic welding. Another problem is precisely controlling the bend of weld joints which is make the railway rail joint crack. Furthermore, it's imperative to make sure the thermite mixture is distributed uniformly to prevent uneven heating and partial fusion. The study investigates the comparative analysis of acceptance criteria for routine tests of aluminothermic welds at Electrified Double Track Project (EDTP) from Gemas to Johor Bahru.  Aluminothermic welding, crucial for ensuring the structural integrity of rail junctions, requires high precision and sensitivity. This study aims to identify the acceptance criteria for routine tests of aluminothermic welds, to analyse a set of routine test results, and identify areas for improvement in the welding process and recommend best practices to ensure compliance with the AS standard. The methodology includes process of preparation of primary data, selection of study area, data collection on routine test results and analyse collected data. The findings indicate that while there is a minimal failure rate and 85% accepted criteria based one specified AS standard and the overall welding quality meets the project's design standards. The study concludes that the welding process applied in the EDTP project demonstrates promising results in terms of weld quality, rail alignment, and joint durability, adhering to the specified standards. Recommendations for further improvement focus on enhancing process reliability and frequent test routines based on specified AS standards.